Factors associated with preterm birth at Wachemo University Nigist Eleni Mohammed memorial hospital, southern Ethiopia: case-control study - Negeso Gebeyehu Gejo; Melaku Tesfaye W/mariam; Biruk Assefa Kebede; Ritbano Ahmed Abdo; Abebe Alemu Anshebo; Hassen Mosa Halil; Biruktawit Fekade Woldu; Nuradin Abusha Katiso (BMC, 2021)
Abstract Background Preterm birth is defined as the birth of a baby before 37 completed weeks of gestation. Worldwide, prematurity is the second foremost cause of death in children under the age of 5 years. Preterm birth also gives rise to short and long term complications. Therefore, the primary aim of this study was to identify the factors associated with preterm birth in Wachemo University Nigist Eleni Mohammed Memorial referral hospital, Hadiya Zone, Southern Ethiopia. Methods An institution-based unmatched case-control study was conducted from July 01, 2018 to June 30, 2019 among mothers who gave birth in Wachemo University Nigest Eleni Mohammed Memorial referral hospital. A retrospective one-year data was retrieved from medical records of mothers with their index neonates. Simple random sampling technique was employed to recruit study participants. SPSS version 20 software was used for data entry and computing statistical analysis. Both bivariable and multivariable logistic regression analyses were used to determine the association of each independent variable with the dependent variable. Odds ratio with their 95% confidence intervals was computed to identify the presence and strength of association, and statistical significance was affirmed if p < 0.05. Result The current study evaluated 213 medical records of mothers with index neonates (71 cases and 142 controls). Urban residency [AOR = 0.48; 95% Cl; 0.239, 0.962], antenatal care follow up [AOR = 0.08; 95 Cl; 0.008, 0.694], premature rupture of membranes [AOR = 3.78; 95% Cl; 1.467, 9.749], pregnancy induced hypertension [AOR = 3.77; 95% Cl; 1.408, 10.147] and multiple pregnancies [AOR = 5.53; 95% Cl; 2.467, 12.412] were the factors associated with preterm birth. More than one-third (36.6%) preterm neonates died in the present study. Conclusions The present study found that urban residency, antenatal care follow up, premature rupture of membranes, pregnancy induced hypertension and multiple pregnancies were factors associated with preterm birth. The mortality among preterm neonates is high. Enhancing antenatal care follow up and early detection and treatment of disorders among pregnant women during antenatal care and undertaking every effort to improve outcomes of preterm birth and reduce neonatal mortality associated with prematurity is decisive.